Professional Employees: Are They Not Vulnerable? - Nazruzila Razniza, Mohd Nadzri; Ong, Tze Chin; Kalaveny, Kanagasingam (INTI International University, 2019)
Employment law is widely defined as a set of laws that regulates employer-employee relationship. Most importantly, the laws offer protection to a contractual party who is at a weaker economic position in a free labour market system. Since workers are commonly the affected party, the employment law places extra attention on securing their rights. The major concern is however, the employment laws may not be extensive to protect all kind of employees particularly professionals. Even if they do, the protection is relatively incomprehensive. Therefore, this paper aims at identifying the legal position of professionals within the scope of employment law and further evaluate the extent employment rights of the professional workers is secured by the existing laws. Finally, it establishes that professionals are sought an equal or similar legal protection to other categories of employees. This paper is a pure doctrinal legal research as it mainly concerns with analysis of the legal principles and how they have been developed and applied.